Evaluating the Cost-Effectiveness and Long-Term Impact of Community-Based First Aid (CBFA) Programs: A Comprehensive Review - Alanazi, Yasir Hadi Falah; Alanazi, Meshal Juayf Abdullah; Alsharare, Mohammad Tabshan Nogaimsh; Al-Hazmi, Ali Ayash Tala; Al Enazi, Abdullah Jeza Awaed; ALrayes, Bader Khaled Salem; Alanazi, Khaled Fayez Zaal; Rasheed Almubadal , Abdulrahman (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Background<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">: Community-Based First Aid (CBFA) programs educate laypeople to respond to emergencies, addressing pressing gaps in pre-hospital care, particularly in resource-scarce settings. Their cost-effectiveness and long-term impact are under-researched despite growing adoption globally. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review evaluates the cost-effectiveness and enduring impact of CBFA programs, identifying barriers and facilitators to inform scalable implementation approaches. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Peer-reviewed studies (2000-2025) from PubMed, Scopus, Web of Science, and grey literature were synthesized narratively. Inclusion criteria were peer-reviewed and grey literature that reported on CBFA effectiveness, costs, or long-term outcomes in any setting. Data were extracted for study design, population, interventions, and outcomes (e.g., ICERs, skill retention), and quality was assessed using GRADE and Cochrane tools. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> CBFA programs are very cost-effective, with ICERs < $500/QALY and benefit-cost ratios as high as 4.2:1. Long-term studies report sustained benefits, including 20-25% reductions in injury hospitalizations and 15-20% improvements in helping behaviors up to 3 years post-training. Challenges: skill decay (20-30% within 6-12 months) and limited funding. Electronic resources and CHW integration support scalability. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> CBFA programs are a cost-effective, equitable emergency preparedness intervention, supporting SDG 3. Policymakers need to prioritize digital integration and strict evaluations for maximal effect.